A novel bismuth-based hybrid material with highly activity for fast removal of rhodamine B under dark conditions. (1st September 2018) - Chu, Kai-Bin; Xie, Jie-Ling; Chen, Wei-Jun; Lu, Wen-Xiu; Song, Jun-Ling; Zhang, Chi
Graphical abstract: A new zero-dimensional hybrid material, namely, (C4 N2 H7 )4 Bi2 Cl10 (1 ) was obtained by slow evaporation method. 1 is composed of protonated 2-methylimidazole cations and [Bi2 Cl10 ] 4− dimer anions, which exhibits high performance for fast degradation of rhodamine B (RhB) at room temperature under dark conditions. The high performance of degradation on dyes indicates it may be used as an effective catalyst to remove organic dyes in wastewater treatment. This study provides an idea to search for new application of hybrid perovskite-materials and shows a facile method to prepare hybrid perovskite-materials under mild conditions. Abstract: The development of sensitive catalysts for fast removal of organic pollutants is crucial for preventing water contamination and improving public health. The recent studies on the degradation of organic pollutants mainly focus on the exploitation of new visible-light-responsive photocatalysts. However, it is still a high challenge to utilize a large fraction of the solar spectrum. Another possible avenue is to degrade organic dyes under dark conditions, which is of great importance for man and the environment. Here, we designed and synthesized a new zero-dimensional hybrid material, namely, (C4 N2 H7 )4 Bi2 Cl10 (1 ) by slow evaporation method. 1 is composed of protonated 2-methylimidazole cations and [Bi2 Cl10 ] 4− dimer anions, which exhibits high performance for fast degradation of rhodamine B (RhB) at room temperature under dark conditions. The high performance of degradation on dyes indicates it may be used as an effective catalyst to remove organic dyes in wastewater treatment.